2016
DOI: 10.5194/acp-16-3327-2016
|View full text |Cite
|
Sign up to set email alerts
|

Molecular corridors and parameterizations of volatility in the chemical evolution of organic aerosols

Abstract: Abstract. The formation and aging of organic aerosols (OA) proceed through multiple steps of chemical reaction and mass transport in the gas and particle phases, which is challenging for the interpretation of field measurements and laboratory experiments as well as accurate representation of OA evolution in atmospheric aerosol models. Based on data from over 30 000 compounds, we show that organic compounds with a wide variety of functional groups fall into molecular corridors, characterized by a tight inverse … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
331
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(387 citation statements)
references
References 126 publications
(194 reference statements)
5
331
4
1
Order By: Relevance
“…Repartitioning of tracers back to the gas phase is not considered in this study. Organosulfates are expected to have very low volatility, with a vapor pressure of 1.7 × 10 −8 Torr at ambient temperature (estimated using eqs 1 and 2 by Li et al 32 ). There is considerable uncertainty surrounding the gas-particle partitioning of tetrols.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Repartitioning of tracers back to the gas phase is not considered in this study. Organosulfates are expected to have very low volatility, with a vapor pressure of 1.7 × 10 −8 Torr at ambient temperature (estimated using eqs 1 and 2 by Li et al 32 ). There is considerable uncertainty surrounding the gas-particle partitioning of tetrols.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…We determined the saturation vapor concentration (C 0 , in µg m −3 at 25 • C) for each of the identified and unidentified species. The values were taken from databases (CRC Handbook, NIST Chemistry WebBook, Yaws, 2015) or estimated based on elemental composition via the parameterization described by Li et al (2016). Species emitted from lower-temperature processes during the fire have a higher fraction of compounds with low volatility compared to the high-temperature processes (later and earlier in the fire shown in Fig.…”
Section: Emission Factors Emission Ratios and Emission Chemistrymentioning
confidence: 99%
“…However, Li et al (2016) parameterized log 10 C * as a function of the number of carbon and oxygen atoms (2D function). The 2D function was fitted to EVAPORATION data for various oxygenated organic compounds.…”
Section: Volatility Distribution From Chemical Analysismentioning
confidence: 99%
“…Using these techniques revealed that the major particle products from α-pinene ozonolysis are highly oxygenated molecules (HOMs), ester dimers, and semi-volatile compounds (Zhang et al, 2015;. Recent studies on the parameterization of saturation concentration (Shiraiwa et al, 2014;Li et al, 2016) and the sensitivity of electrospray ionization mass spectrometry (Kruve et al, 2013;Heinritzi et al, 2016) is helpful to evaluate SOA volatility using mass analysis data. 50…”
Section: Introductionmentioning
confidence: 99%